Management of Student Planning at SMAN 5 Cirebon City - Rakhman, Putri Yanita (JIEM (Journal of Islamic Education Management), 2022)
This study aims to identify specifics about student planning management at SMAN 5 Cirebon City. In this study, researchers used a descriptive qualitative approach. Data collection techniques are carried out in a triangulation, analytical is inductive planning management in detail and accurately according to observational data, interviews with related parties and valid written data. The results of this study show that the planning management of students at SMAN 5 Cirebon City can be categorized as quite good and in accordance with the procedures that have been set by the West Java Provincial Education Office. Management of student planning at SMAN 5 Cirebon City is also in accordance with planning steps such as analysis of student needs, student recruitment, student selection, student orientation, student placement, to recording and reporting of students organized by the student department according to standards or techinica instruction that have been given by the government.